ADVANCEMENT OF THE LINGUO-METHODOLOGICAL REASONING OF AN EDUCATOR IN A FOREIGN LANGUAGE - Pardayeva Diyora Tokhirovna (Bright Mind Publishing, 2025)
The problem of developing lingvomethodological thinking remains relevant today. Lingvo-methodical thinking is a complex thinking activity of the pedagogue aimed at selecting, adapting and updating language teaching methods.This article sheds light on the problem of lingvodidactic thinking in modern science and explores various interpretations of this concept.
Keywords: Linguo methodical thinking; foreign language teacher; teacher education; methodical competence; reflective practice; professional development.